Interfaces between family and bullying: a literature systematic review - Abanto Vélez, Walter Iván (2022)
The objective of this research was to analyze the different theories of interfaces between family and school bullying, trying to know the depth of the investigations between family and bullying. The design was a systematic review, which consists of a theoretical review of research carried out in recent years, selecting articles published in scientific psychology journals indexed in electronic databases, by adopting predetermined criteria. The study sample consisted of 40 research articles taken from psychology, education and medicine journals such as: Latin American Journal of Psychology, International Journal of Developmental and Educational Psychology, School and Educational Psychology, Psychosocial Intervention. The results show that the studies carried out on the topic of interfaces between family and bullying report a direct relationship, this means that families influence student behavior within educational institutions.